LIKARI (Five Words in A Day) Application to Improve Vocabulary Mastery in Japanese Language Learning - Kartika, Diana; Oslan Amril; Tienn Immerry; Aulya Chasovy; Arief Juneirul Pratama (Universitas Pendidikan Ganesha, 2023)
Students experience several obstacles in understanding and mastering Japanese vocabulary. Students need to have appropriate and exciting strategies for learning vocabulary. Therefore, this research aims to develop interactive learning media using an Android-based application called